ROALD DAHL’S USE OF LANGUAGE PLAY IN CHARLIE AND THE GREAT GLASS ELEVATOR - Trisnowati Tanto (Sosiohumaniora, 2008)
Nowadays playing with language has already become a common thing that we do in our daily conversation, usually with the expected purpose of making an utterance more attractive, humorous, and entertaining. If further analysed, linguistically, language play actually makes use of the linguistic elements such as those in the phonological, morphological, semantic and graphological areas. In children’s books, language play is often used as a tool to make the stories more attractive for children. This is gained from the pleasant sounds as well as humorous meanings produced and also from more detailed and clearer descriptions of the stories. These are the effects produced by the use of the various items of language play, such as the use of unique similes, homophones and homonyms, contradictory words, allusion, alliterations, spelling, etc. These all are the reasons for a novel being special and unique. Key words: Language play, linguistic elements, children.